Pengaruh Penerapan Proyek PAQ terhadap Literasi STEM Aspek Sikap pada Topik Pemanasan Global dalam Masa Pandemi Covid-19 - Rivana Usgianti Tanti (Lembaga Marwah Rakyat, 2022)
The Covid-19 pandemic that has hit the world has also affected changes in the education system in Indonesia. Not all schools have the ability to implement online learning which requires an internet network and a set of advanced media. Schools located in areas with limited internet networks, poor community economic conditions, and the difficulty of reaching students' residences as in SMP Negeri 1 Batang Tuaka require special efforts from teachers to create the most realistic learning innovations for students. This study aimed to determine the effect of the use of the Al-Qur'an Verse Search project (PAQ) on improving STEM literacy on the attitude aspect on the topic of Global Warming at SMP Negeri 1 Batang Tuaka during the Covid-19 pandemic. This research was a quasi-experimental study with 36 students of class VII at SMP Negeri 1 Batang Tuaka in the 2021/2022 academic year which is divided into two classes, namely the control class and the experimental class. The instrument of this research is the attitude of students' interest in STEM and students' concern for the environment. Data were analyzed using SPSS 22 and the